Intratracheal Injection into Rats of Size-graded Silica Particles. Issue 1 (January 1966) - Goldstein, B.; Webster, I.
Abstract : An experiment is described in which suspensions of size-graded silica particles of less than 1 μ, 1 to 3 μ, and 2 to 5 μ nominal size ranges and of equal surface area (600 sq. cm./ml.) were injected intratracheally into rats. After four months the rats were killed and the lungs were examined histologically for the grade of fibrosis and chemically for the silica and collagen content. The results were analysed statistically and it was found that, under the experimental conditions described, the degree of fibrosis produced by the two large size fractions was more than that produced by the under 1 μ particles and was apparently related to the quantity (by weight) of the silica injected or the size of the particles and not to the surface area.